Legality of Implementing an Embargo in Efforts to Resolve Armed Conflicts Between Countries - Suling, Derfy Rizky (Fakultas Syariah Institut Agama Islam Negeri Palu, 2024)
Embargo have become one of the common strategies used by states in responding to violations of international law by other states including when there is an armed conflict between states. However, the application of embargoes tends to worsen the atmosphere of conflict, disrupt international politics and cause significant impacts in many countries which raises the question of how important the application of embargoes as an effort to resolve conflicts. This problem will also target the legality of such actions in the context of the principles of international law governing state sovereignty, human rights, and international trade rules. With a normative legal analysis approach, this research aims to examine the international legal framework governing the implementation of embargoes, which reveals that the use of economic sanctions has been a common practice found in international law for many years and has developed into an international custom.